Do the physical and environment PETTLEP elements predict sport imagery ability? - Anuar, N.; Williams, S. E.; Cumming, J. (European Journal of Sport Science, 2017)
The present study aimed to examine whether physical and environment elements of PETTLEP imagery relate to the ability to image five types of sport imagery (i.e. skill, strategy, goal, affect and mastery). Two hundred and ninety participants (152 males, 148 females; Mage = 20.24 years, SD = 4.36) from various sports completed the Sport Imagery Ability Questionnaire (SIAQ), and a set of items designed specifically for the study to assess how frequently participants incorporate physical (e.g. `I make small movements or gestures during the imagery`) and environment (e.g. `I image in the real training/competition environment`) elements of PETTLEP imagery. Structural equation modelling tested a hypothesised model in which imagery priming (i.e. the best fitting physical and environment elements) significantly and positively predicted imagery ability of the different imagery types (skill, ß = 0.38; strategy, ß = 0.23; goal, ß = 0.21; affect, ß = 0.25; mastery, ß=0.22). The model was a good fit to the data: (174) = 263.87, p < .001, CFI = .96, TLI = .95, SRMR = .09, RMSEA = 0.05 (90% CI = 0.03-0.05). Findings displayed that priming imagery with physical and environment elements is associated with better skill, strategy, goal, affect and mastery imagery ability. The findings extend models of imagery use by indicating that how athletes images may influence their imagery ability.